Konsep Keadilan Sosial Pancasila Dalam Hukum Ekonomi Dan Implementasinya Di Pesantren Iserta Madrasah Diniyyah - Nonik Anggrainita; Alya Al izzati Rofidah; Septia Dwi Ainur Rahma; Adella Putri Masyithoh (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The fifth principle of Pancasila, namely social justice for all Indonesian people, serves as a fundamental foundation in shaping the national legal and economic systems. This principle emphasizes equitable access to resources, protection for economically disadvantaged groups, and the reduction of social inequality. In the realm of economic law, the value of social justice in Pancasila is reflected in policies that support people-centered economies, such as cooperatives and micro, small, and medium enterprises (MSMEs). This study aims to examine in depth the application of these values in economic legal practices, particularly within pesantren and madrasah diniyyah as traditional Islamic educational institutions. The research employs a descriptive qualitative approach, using data collection methods such as literature review, direct observation, and interviews with pesantren caretakers, madrasah diniyyah administrators, and sharia economic practitioners. Findings indicate that these institutions have adopted the principle of social justice through various community-based economic activities, such as student cooperatives, pesantren business units, and the productive management of zakat and waqf funds. These practices not only promote the economic independence of the institutions but also contribute to the empowerment of surrounding communities. Nevertheless, several challenges remain, including limited understanding of economic law regulations, low financial literacy, and suboptimal collaboration between the government and Islamic educational institutions in developing an economy rooted in Pancasila values. Therefore, more inclusive policies, ongoing legal assistance, and the integration of social justice values into diniyyah education curricula are needed. This research is expected to contribute to strengthening the national economic legal framework grounded in the noble values of Pancasila, particularly within the context of Islamic education.